Purchasing Power Parity (PPP) in a Transition Economy - Cambodia: Empirical Evidence from Bilateral Exchange Rates - Tuck, Cheong Tang; Liew, Venus Khim-Sen (Monash University Bussiness anf Economics, 2009)
This study contributes to the existing literature by examining the validity of PPP hypothesis for Cambodia. The standard unit root tests (ADF and PP) and the panel unit root tests fail to support PPP hypothesis for the nine Cambodia’s trading partners. The unit root tests with structural break support the PPP hypothesis for the bilateral real exchange rates of Euro, Indonesia rupiah, Malaysia ringgit, and Singapore dollar. This finding is found to be relevant for ‘de-dollarization’ strategy in Cambodia, and in responding to recent global financial crisis (2007-2008).